Transaction Analysis for Operational Optimization in Transjakarta Public Transportation System - Lapatta, Nouval Trezandy; Hendra, Andi; Firzatullah, Raden Muhamad (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2024)
This study presents a comprehensive exploratory data analysis (EDA) of transaction data within the Transjakarta public transportation system, focusing on routes, passenger flow, and congestion patterns. Leveraging tap-in and tap-out transaction records collected through payment cards, the research aims to provide actionable insights for optimizing operational efficiency and enhancing service quality. By analyzing transaction data, the study identifies busy routes, peak hours, and passenger distribution across different modes of transportation, including big bus (BRT), medium and big bus (non-BRT), and mini-bus (Mikrotrans). Moreover, the research investigates correlations between transaction volume and traffic congestion levels, enabling the identification of areas prone to delays and bottlenecks. The findings of this analysis offer valuable information for route planning, scheduling adjustments, and infrastructure improvements within the Transjakarta system. By optimizing resources based on data-driven insights, the study seeks to contribute to the enhancement of public transportation services, promoting accessibility, reliability, and sustainability in urban mobility.